LC‐ESI‐QTOF/MS characterization of antimicrobial compounds with their action mode extracted from vine tea (Ampelopsis grossedentata) leaves. Issue 2 (19th January 2022) - Umair, Muhammad; Sultana, Tayyaba; Xiaoyu, Zhu; Senan, Ahmed M.; Jabbar, Saqib; Khan, Labiba; Abid, Muhammad; Murtaza, Mian Anjum; Kuldeep, Dhama; Al‐Areqi, Niyazi A. S.; Zhaoxin, Lu
Abstract: Vine tea ( Ampelopsis grossedentata ) is a tea plant cultivated south of the Chinese Yangtze River. It has anti‐inflammatory properties and is used to normalize blood circulation and detoxification. The leaves of vine tea are the most abundant source of flavonoids, such as dihydromyricetin and myricetin. However, as the main bioactive flavonoid in vine tea, dihydromyricetin was the main focus of previous research. This study aimed to explore the antibacterial activities of vine tea against selected foodborne pathogens. The antimicrobial activity of vine tea extract was evaluated by the agar well diffusion method. Cell membrane integrity and bactericidal kinetics, along with physical damage to the cell membrane, were also observed. The extract was analyzed using a high‐performance liquid chromatography‐diode array detector (HPLC‐DAD), and the results were confirmed using a modified version of a previously published method that combined liquid chromatography and electrospray‐ionized quadrupole time‐of‐flight mass spectrometry (LC‐ESI‐QTOF/MS). Cell membrane integrity and bactericidal kinetics were determined by releasing intracellular material in suspension and monitoring it at 260 nm using an ultraviolet (UV) spectrophotometer. A scanning electron microscope (SEM) was used to detect morphological alterations and physical damage to the cell membrane. Six compounds were isolated successfully: (1) myricetin (C15 H10 O8 ), (2) myricetin 3‐O‐rhamnoside (C21 H20 O12 ), (3) 5, 7, 8, 3, 4‐pentahydroxyisoflavone (C15 H10 O7 ), (4) dihydroquercetin (C15 H12 O7 ), (5) 6, 8‐dihydroxykaempferol (C15 H10 O8 ), and (6) ellagic acid glucoside (C20 H16 O13 ). Among these bioactive compounds, C15 H10 O7 was found to have vigorous antimicrobial activity against Bacillus cereus (AS11846) and Staphylococcus aureus (CMCCB26003). A dose‐dependent bactericidal kinetics with a higher degree of absorbance at optical density 260 (OD260 ) was observed when the bacterial suspension was incubated with C15 H10 O7 for 8 h. Furthermore, a scanning electron microscope study revealed physical damage to the cell membrane. In addition, the action mode of C15 H10 O7 was on the cell wall of the target microorganism. Together, these results suggest that C15 H10 O7 has vigorous antimicrobial activity and can be used as a potent antimicrobial agent in the food processing industry. Abstract : This study explored the antimicrobial utility of vine tea ( Ampelopsis grossedentata ) against disease‐causing foodborne pathogens.